Establishment and Verification of Synchronous Metastatic Nomogram for Gastrointestinal Stromal Tumors (GISTs): A Population-Based Analysis - Yuqiang Li; Guangfeng Zhang; Xiangping Song; Lilan Zhao; Cenap Güngör; Dan Wang; Wenxue Liu; Yan Huang; Fengbo Tan (Gastroenterology Research and Practice)
Aim. Assess the risk of synchronous metastasis and establish a nomogram in patients with GISTs. Methods. Surveillance, Epidemiology and End Results database (2004-2014) was accessed. With the logistic regression model as the basis, a nomogram was constructed. Results. 7,256 target patients were contained in our study. The nomogram discrimination for mGIST prediction revealed that tumor size contributed most to synchronous metastasis, followed by lymph nodes, extension, pathologic grade, tumor location, and mitotic count. C-index values of predictions were 0.821 (95% CI, 0.805-0.836) and 0.815 (95% CI, 0.800-0.831), and Brier score were 0.109 and 0.112 in training and validation group, respectively. The value of area under the ROCs were 0.813 (p<0.001) in the primary cohort and 0.819 (p<0.001) in the validation cohort. Through the calibration curves (as seen in the figures), nomogram prediction proved to have excellent agreement with actual metastatic diseases. Conclusion. A new nomogram was created that can evaluate synchronous metastatic diseases in patients with GISTs.